Health Literacy as a Determinant of Family Preparedness in Facing Disasters - Sumarah (Miracle Journal Get Press, 2026)
Family preparedness is an important component in disaster mitigation and response efforts at the community level. However, the level of community preparedness is often influenced by individuals' ability to understand and use health information accurately. Health literacy plays a crucial role in enhancing the capacity of families to recognise risks, make informed decisions, and take effective preventive and disaster response actions. This study aims to analyse the relationship between health literacy and family preparedness in facing disasters. This study uses an analytical observational design with a cross-sectional approach. The research population consists of families living in disaster-prone areas. The sampling technique used is the probability sampling method. A total of 210 families met the inclusion criteria and were involved as research respondents. Data collection was conducted using a health literacy and family preparedness questionnaire that had been tested for validity and reliability. Data analysis was conducted univariately, bivariately using correlation tests, and multivariately using linear regression to identify factors influencing family preparedness. The research results show that a higher level of health literacy is significantly associated with a better level of family preparedness in facing disasters. These findings indicate that health literacy is one of the important determinants in improving family preparedness. Therefore, efforts to improve public health literacy need to be an integral part of the disaster preparedness strengthening strategy at the family and community levels.